The Determinants of U.S Private Manufacturing Investments in Africa - Agodo, Oriye (Journal of International Business Studies, 1978)
An inquiry into the determinants of U.S. private manufacturing investments in Africa shows that corporate decisions to undertake manufacturing investments abroad are essentially determined by the expected rate of return on investment, the size of the domestic market, the presence of needed raw materials, a sufficiently developed infrastructure, political stability and a favorable investment climate, and good prospects for the growth of private enterprise in the host country. On the other hand, the rate of growth of the domestic market, relatively low overseas wages, and tax concessions and tariff protection offered by host governments have nonsignificant influence on the foreign investment decision.